Design of ultra‐low noise, wideband low‐noise amplifier for highly survival radar receiver. Issue 6 (1st November 2016) - Ray, Arun Kumar; Shit, Rathin Chandra
Abstract : High electron mobility transistors (HEMTs) play a crucial role in microwave low‐noise amplifier (LNA) and are used in radar receiver, software defined radio and digital radio frequency. A novel technique is used to design and fabricate a high‐performance wideband LNA for 5.4–5.9 GHz based on fully stabilised InGaAs pseudo‐morphic HEMT (pHEMT) 0.15 µm technology. With the Agilent Advanced Design System simulation tool, a C‐band (5.4–5.9 GHz) two‐stage LNA using pHEMT based on monolithic microwave integrated circuit (MMIC) technology has been designed: noise figure <1 dB, power gain of 18 dB, output 1 dB compression >13 dBm and OIP3 >24 dBm, lower value of input/output return loss reflects the accuracy of impedance matching network at input and output sides of amplifier, full band unconditional stability. In this study, it is shown that the InGaAs pHEMT has the ability to handle high power to make it the perfect technology candidate for highly survival radar receiver component and survival up to 37 dBm input power level is demonstrated. The circuit based in the proposed technology shows comparable low noise figure, decent gain, with high dynamic range and high survivability. Finally, the simulation results and fabricated device results are in good agreement and superior than the earlier reported design.